Melampaui Paradigm Wars: Pragmatisme sebagai Meta-Framework untuk Integrasi Tradisi Filosofis dalam Mixed Method Research - Khabibullah, Muttaqin; Alimin; Sholahuddin, Gus Malik Imam (Jurnal Studi Multidisiplin Qomaruna, 2025)
In recent decades, MMR has emerged as the third methodological movement due to the “paradigm wars” between quantitsative and qualitative. The philosophy of pragmatism is often associated with MMR because of its flexibility in integrating various methods to answer research needs. However, there are still major challenges in integrating the underlying philosophies, especially the aspects of ontology, epistemology, and methodology. This study aims to analyze how the philosophy of pragmatism can be used as a meta-framework in MMR; how pragmatism is able to accommodate positivism, constructivism, critical realism, and transformative-emancipatory in various MMR models; and to develop a conceptual framework to understand the ontological, epistemological, and methodological positions of this integration. The approach used in this study is literature synthesis with the narrative review method. This study produces findings that pragmatism in MMR acts as a meta-framework that can combine various research methods by accommodating various relevant philosophical views. The results of this study also found that pragmatism is able to accommodate various philosophical paradigms by accepting that both quantitative and qualitative (as well as other methods) have equal value and complement each other in producing scientific knowledge. Furthermore, the results of this study also present a conceptual framework that can position ontology, epistemology, and methodology in MMR integration.